The SARS-CoV-2 spike protein is vulnerable to moderate electric fields - Claudia R. Arbeitman (Nature Portfolio, 2021)
The SARS-CoV-2 Spike protein is essential for viral infectivity and binds to the host receptor ACE2. Here, the authors present MD simulations of the Spike protein and its variants of concern and observe that the Spike protein is destabilised by moderate static electric fields, and undergoes field-induced conformational changes that hinder binding to ACE2.